Hysterectomy as a life saving measure in choriocarcinoma: a case report - Prasanna Venugopalan,; Vattaparambil, Fathima; Nair, Vidhu Venugopalan; Kutty, Sathiamma Puthuvilayil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Choriocarcinoma (CC) is a highly malignant tumour originating in the trophoblastic tissue. Typically occurring following molar pregnancies, its occurrence after full-term pregnancies is exceptionally uncommon. Hysterectomy has a limited role in the management of gestational trophoblastic neoplasia because of the high effectiveness of chemotherapy and the young age of patients. We present a case report of a 31-year-old patient who was referred to our hospital with massive vaginal bleeding, 20 days following evacuation of molar pregnancy.